Preparation method and application of functional filler
By preparing In2O3/CA/PGMA type functional fillers and adding them to the thermoplastic resin, the problem that thermoplastic resins are difficult to have excellent mechanical properties and antibacterial properties at the same time is solved, and the versatility of thermoplastic resin composites is improved.
Patent Information
- Application Number
- CN202311087595.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-28
- Publication Date
- 2025-02-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
While existing thermoplastic resins have excellent mechanical properties, they are difficult to have excellent antibacterial properties at the same time, and cannot meet the multifunctional needs.
By preparing a functional filler, including In2O3, chlorogenic acid (CA), and glycidyl methacrylate, a functional filler of the In2O3/CA/PGMA type is formed and added to the thermoplastic resin to improve its mechanical properties and antibacterial properties.
The mechanical properties and antibacterial properties of thermoplastic resins have been improved, and a multifunctional thermoplastic resin composite material has been formed, suitable for applications in multiple fields.
Smart Images

Figure BDA0004416583770000041 
Figure BDA0004416583770000061 
Figure BDA0004416583770000071
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of functional fillers, and in particular relates to a method for preparing a functional filler, and application of the functional filler prepared by the preparation method in a thermoplastic resin composite material. Background Art
[0002] As a widely used polymer polyester resin, thermoplastic resin has excellent performance. At present, it is usually given corresponding properties by adding some functional additives. With the expansion of the application field of polymer materials, the demand for multifunctional thermoplastic resins is increasing. For example, in some specific fields, thermoplastic resins are required to have excellent mechanical properties and excellent antibacterial properties. Therefore, the development of functional fillers with multiple functions has become a research hotspot in this field.
[0003] The present invention is devoted to illustrating a method for preparing a functional filler to improve the mechanical properties and antibacterial properties of thermoplastic resin. Summary of the invention
[0004] In view of this, it is necessary for the present invention to provide a method for preparing a functional filler. The functional filler prepared by the preparation method is applied to a thermoplastic resin to improve the mechanical properties and antibacterial properties of the thermoplastic resin.
[0005] In order to achieve the above object, the present invention adopts the following technical solutions:
[0006] The present invention first provides a method for preparing a functional filler, comprising the following steps:
[0007] Get In2O3;
[0008] In2O3, an initiator, a cross-linking agent, anhydrous ethanol, deionized water, chlorogenic acid, and glycidyl methacrylate were reacted in a water bath at 40-60°C for 8-12 hours to obtain a functional filler having a composition of In2O3 / CA / PGMA.
[0009] In a further embodiment, the preparation of In2O3 comprises the following steps:
[0010] Take indium nitrate, ammonia water and deionized water, stir and react at 40-60°C for 6-8h to prepare solution A;
[0011] The solution A is filtered, washed, dried, and then calcined at 680-720° C. for 8-16 hours to obtain In 2 O 3 .
[0012] The reaction process of In2O3 prepared in this application is as follows:
[0013] In(NO3)3+NH3·H2O→In(OH)3+NH4NO3
[0014] 2In(OH)3→In2O3+3H2O.
[0015] In a further embodiment, in the step of preparing solution A, the mass ratio of indium nitrate, ammonia water and deionized water is (30-40): (28-32): (60-80).
[0016] In a further embodiment, the mass ratio of In2O3, initiator, cross-linking agent, anhydrous ethanol, deionized water, chlorogenic acid, and glycidyl methacrylate is (30-40): (0.1-0.3): (0.2-0.4): (30-40): (60-80): (18-24): (16-20).
[0017] In a further embodiment, the initiator is ammonium persulfate; and the cross-linking agent is N,N-methylenebisacrylamide.
[0018] The present invention also provides the use of the functional filler as described above in the preparation of a thermoplastic resin composite material.
[0019] The present invention further provides a thermoplastic resin composite material, which is prepared by weight from 80 to 120 parts of a thermoplastic resin, 8 to 12 parts of a functional filler, and 0.1 to 0.5 parts of an antioxidant;
[0020] Wherein, the functional filler is prepared by the preparation method as described above.
[0021] In a further embodiment, the thermoplastic resin is selected from one of polyethylene (PE), polypropylene (PP), polystyrene (PS), polybutylene terephthalate (PBT), and polyamide 6 (PA6).
[0022] In a further embodiment, the antioxidant is selected from one of antioxidant 168, antioxidant 1010, and antioxidant 1330, or a mixture of two or more thereof.
[0023] The present invention further provides a method for preparing the thermoplastic resin composite material as described above, comprising the following steps:
[0024] The thermoplastic resin, the functional filler and the antioxidant are uniformly mixed according to a ratio to obtain a mixture;
[0025] The mixed material is extruded and granulated through a twin-screw extruder to obtain a thermoplastic resin composite material.
[0026] Beneficial effects of the present invention:
[0027] In this application, In2O3 is used as a raw material. Under the action of a cross-linking agent and an initiator, glycidyl methacrylate is polymerized into polyglycidyl methacrylate. Polyglycidyl methacrylate, In2O3, and chlorogenic acid (CA) form an interpenetrating three-dimensional network structure to form a functional filler with a stable structure and a composition of In2O3 / CA / PGMA. Among them, chlorogenic acid (CA) has a catechol structure, and its catechol group can be adsorbed on the surface of the bacterial cell wall, destroying the cell wall structure and the permeability of the cell membrane, and then killing the bacteria, thereby improving the antibacterial properties of the thermoplastic resin. The presence of epoxy groups in polyglycidyl methacrylate improves the interfacial compatibility between the thermoplastic resin and In2O3, and improves the mechanical properties of the thermoplastic resin. DETAILED DESCRIPTION
[0028] Embodiments of the present invention are described in detail below. The embodiments described below are exemplary and are only used to explain the present invention, and should not be construed as limiting the present invention.
[0029] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. In addition, unless otherwise specified, methods that do not specifically record conditions or steps are conventional methods, and the reagents and materials used can be obtained from commercial sources.
[0030] The raw material information used in the following examples and comparative examples is as follows:
[0031] PBT (model 2002U), Polyplastics, Japan; PP (model Z30S), Maoming Petrochemical; PE (model 5070), Panjin Ethylene; PA6 (model CM1017), Toray, Japan; PS (model 350), Guoqiao, Taiwan, China;
[0032] Deionized water, Xiamen Aoquan Environmental Protection Technology Co., Ltd.; glycidyl methacrylate, Jinan Mingwei Chemical Co., Ltd.; In2O3, Shanghai Yingcheng New Materials Co., Ltd.; anhydrous ethanol, Shandong Taixi Chemical Co., Ltd.; deionized water, Xiamen Aoquan Environmental Protection Technology Co., Ltd.; ammonium persulfate, Shandong Chuangying Chemical Co., Ltd.; N,N-methylenebisacrylamide, Jinan Jiayang Chemical Co., Ltd.; chlorogenic acid (CA), Changsha Shanghe Biotechnology Co., Ltd.; indium nitrate, Hubei Chengfeng Chemical Co., Ltd.; ammonia water, Chengdu Zhongzhi Chemical Co., Ltd.; antioxidants (models Irganox168, Irganox1010, Irganox1330), BASF.
[0033] The test methods and test conditions used for the composite materials obtained in the following examples and comparative examples are as follows:
[0034] Tensile strength: ASTM D638, the tensile specimen used is (170.0±5.0)mm×(13.0±0.5)mm×(3.2±0.2)mm, and the tensile rate is 50mm / min;
[0035] Izod notched impact strength: ASTM D256, specimen model: (125.0±5.0)mm×(13.0±0.5)mm×(3.2±0.2)mm, notch is machined, notch depth is (2.6±0.2)mm;
[0036] Flexural strength: ASTM D790, the bending specimen used in the test is (125.0±5.0)mm×(13.0±0.5)mm×(3.2±0.2)mm, and the bending rate is 1.25mm / min;
[0037] Antibacterial rate: JIS Z 2801, using (50mm±2mm)×(50mm±2mm)×(2mm±0.1mm) test piece, test after 24 hours of inoculation.
[0038] Example 1
[0039] Preparation of functional fillers
[0040] (1) Weigh 300 g of indium nitrate, 280 g of ammonia water, and 600 g of deionized water, place them in a reaction vessel, and stir and react at 40° C. for 6 h to prepare solution A;
[0041] (2) Filtering, washing, and drying solution A, and calcining it at 680° C. in a muffle furnace for 8 h to obtain In2O3;
[0042] (3) Weigh 300 g of In2O3, 1 g of initiator ammonium persulfate, 2 g of cross-linking agent N,N-methylenebisacrylamide, 300 g of anhydrous ethanol, 600 g of deionized water, 180 g of chlorogenic acid (CA), and 160 g of glycidyl methacrylate, place them in a reaction vessel, react in a 40°C water bath for 8 h, filter, wash, and dry to obtain a functional filler of the In2O3 / CA / PGMA type, recorded as M1.
[0043] Preparation of thermoplastic resin composites
[0044] (1) Weigh 80 parts of PP, 8 parts of functional filler M1, and 0.1 parts of Irganox 1010 according to the weight ratio, mix and stir evenly to obtain a mixture;
[0045] (2) The mixed material obtained in step (1) is extruded and granulated from a twin-screw extruder to obtain a PP composite material, which is recorded as P1.
[0046] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 170°C, the temperature of the second temperature zone is 220°C, the temperature of the third temperature zone is 230°C, the temperature of the fourth temperature zone is 230°C, the temperature of the fifth temperature zone is 230°C, the temperature of the sixth temperature zone is 230°C, the head temperature of the twin-screw extruder is 230°C, and the screw speed is 220r / min.
[0047] Comparative Example 1
[0048] Compared with Example 1, this comparative example only has a different functional filler, and the filler in this comparative example is In2O3 calcined in Example 1. The preparation of the thermoplastic resin composite material in this comparative example is as follows:
[0049] (1) 80 parts of PP, 8 parts of In2O3 calcined in Example 1, and 0.1 parts of Irganox1010 were weighed and mixed and stirred to obtain a mixture;
[0050] (2) Extruding the mixture obtained in step (1) through a twin-screw extruder and granulating it to obtain a PP composite material, which is recorded as D1.
[0051] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 170°C, the temperature of the second temperature zone is 220°C, the temperature of the third temperature zone is 230°C, the temperature of the fourth temperature zone is 230°C, the temperature of the fifth temperature zone is 230°C, the temperature of the sixth temperature zone is 230°C, the head temperature of the twin-screw extruder is 230°C, and the screw speed is 220r / min.
[0052] The PP composite materials prepared in Example 1 and Comparative Example 1 were made into specimens using an injection molding machine for testing. The test results are shown in Table 1.
[0053] Table 1 Test results of relevant properties of PP composite materials prepared in Example 1 and Comparative Example 1
[0054]
[0055] It can be seen from the test results in Table 1 that the mechanical properties and antibacterial properties of the PP composite material prepared in Example 1 are better than those of Comparative Example 1.
[0056] Example 2
[0057] Preparation of functional fillers
[0058] (1) Weigh 400 g of indium nitrate, 320 g of ammonia water, and 800 g of deionized water, place them in a reaction vessel, and stir and react at 60° C. for 8 h to prepare solution A;
[0059] (2) Filtering, washing, and drying solution A, and calcining it at 720° C. in a muffle furnace for 16 h to obtain In2O3;
[0060] (3) Weigh 400 g of In2O3, 3 g of initiator ammonium persulfate, 4 g of cross-linking agent N,N-methylenebisacrylamide, 400 g of anhydrous ethanol, 800 g of deionized water, 240 g of chlorogenic acid (CA), and 200 g of glycidyl methacrylate, place them in a reaction vessel, react in a 60°C water bath for 12 h, filter, wash, and dry to obtain a functional filler of the In2O3 / CA / PGMA type, recorded as M2.
[0061] Preparation of thermoplastic resin composites
[0062] (1) Weigh 120 parts of PBT, 12 parts of functional filler M2, 0.1 parts of antioxidant Irganox 1010, 0.2 parts of antioxidant Irganox 168, and 0.2 parts of antioxidant Irganox 1330 according to weight, mix and stir evenly to obtain a mixture;
[0063] (2) The mixed material obtained in step (1) is extruded and granulated from a twin-screw extruder to obtain a PBT composite material, which is denoted as P2.
[0064] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 200°C, the temperature of the second temperature zone is 230°C, the temperature of the third temperature zone is 240°C, the temperature of the fourth temperature zone is 240°C, the temperature of the fifth temperature zone is 240°C, the temperature of the sixth temperature zone is 240°C, the head temperature of the twin-screw extruder is 240°C, and the screw speed is 300r / min.
[0065] Comparative Example 2
[0066] Compared with Example 2, this comparative example only has a different functional filler, and the filler in this comparative example is In2O3 calcined in Example 2. The specific steps for preparing the thermoplastic resin composite material in this comparative example are as follows:
[0067] (1) According to the weight ratio, 120 parts of PBT, 12 parts of In2O3 calcined in Example 2, 0.1 parts of antioxidant Irganox1010, 0.2 parts of antioxidant Irganox168, and 0.2 parts of antioxidant Irganox1330 were weighed, mixed and stirred to obtain a mixture;
[0068] (2) The mixed material obtained in step (1) is extruded and granulated from a twin-screw extruder to obtain a PBT composite material, which is recorded as D2.
[0069] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 200°C, the temperature of the second temperature zone is 230°C, the temperature of the third temperature zone is 240°C, the temperature of the fourth temperature zone is 240°C, the temperature of the fifth temperature zone is 240°C, the temperature of the sixth temperature zone is 240°C, the head temperature of the twin-screw extruder is 240°C, and the screw speed is 300r / min.
[0070] The PBT composite materials prepared in Example 2 and Comparative Example 2 were made into specimens using an injection molding machine for testing. The test results are shown in Table 2.
[0071] Table 2 Test results of relevant properties of PBT composite materials prepared in Example 2 and Comparative Example 2
[0072]
[0073] It can be seen from the test results in Table 2 that the mechanical properties and antibacterial properties of the PBT composite material prepared in Example 2 are better than those of Comparative Example 2.
[0074] Example 3
[0075] Preparation of functional fillers
[0076] (1) Weigh 350 g of indium nitrate, 300 g of ammonia water, and 700 g of deionized water, place them in a reaction vessel, and stir them at 50° C. for 7 h to prepare solution A;
[0077] (2) Filtering, washing, and drying solution A, and calcining it at 700°C in a muffle furnace for 12 h to obtain In2O3;
[0078] (3) Weigh 350 g of In2O3, 2 g of initiator ammonium persulfate, 3 g of cross-linking agent N,N-methylenebisacrylamide, 350 g of anhydrous ethanol, 700 g of deionized water, 210 g of chlorogenic acid (CA), and 180 g of glycidyl methacrylate, place them in a reaction vessel, react in a 50°C water bath for 10 h, filter, wash, and dry to obtain a functional filler of the In2O3 / CA / PGMA type, recorded as M3.
[0079] Preparation of thermoplastic resin composites
[0080] (1) Weigh 100 parts of PE, 10 parts of functional filler M3, 0.1 parts of antioxidant Irganox 168, and 0.2 parts of antioxidant Irganox 1010 according to weight, mix and stir evenly to obtain a mixture;
[0081] (2) The mixed material obtained in step (1) is extruded and granulated from a twin-screw extruder to obtain a PE composite material, which is denoted as P3.
[0082] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 120°C, the temperature of the second temperature zone is 180°C, the temperature of the third temperature zone is 180°C, the temperature of the fourth temperature zone is 180°C, the temperature of the fifth temperature zone is 180°C, the temperature of the sixth temperature zone is 180°C, the head temperature of the twin-screw extruder is 180°C, and the screw speed is 300r / min.
[0083] Comparative Example 3
[0084] Compared with Example 3, this comparative example only has a different functional filler, and the filler in this comparative example is In2O3 calcined in Example 3. The preparation of the thermoplastic resin composite material in this comparative example is as follows:
[0085] (1) According to the weight ratio, 100 parts of PE, 10 parts of In2O3 calcined in Example 3, 0.1 parts of antioxidant Irganox168, and 0.2 parts of antioxidant Irganox1010 were weighed, mixed and stirred to obtain a mixture;
[0086] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PE composite material, which is recorded as D3.
[0087] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 120°C, the temperature of the second temperature zone is 180°C, the temperature of the third temperature zone is 180°C, the temperature of the fourth temperature zone is 180°C, the temperature of the fifth temperature zone is 180°C, the temperature of the sixth temperature zone is 180°C, the head temperature of the twin-screw extruder is 180°C, and the screw speed is 300r / min.
[0088] The PE composite materials prepared in Example 3 and Comparative Example 3 were made into specimens using an injection molding machine for testing. The test results are shown in Table 3.
[0089] Table 3 Test results of relevant properties of PE composite materials prepared in Example 3 and Comparative Example 3
[0090]
[0091] It can be seen from the test results in Table 3 that the mechanical properties and antibacterial properties of the PE composite material prepared in Example 3 are better than those of Comparative Example 3.
[0092] Example 4
[0093] Preparation of functional fillers
[0094] (1) Weigh 335 g of indium nitrate, 315 g of ammonia water, and 785 g of deionized water, place them in a reaction vessel, and stir and react at 55° C. for 8 h to prepare solution A;
[0095] (2) Filter, wash, and dry solution A, and calcine in a muffle furnace at 715° C. for 9 h to obtain In2O3;
[0096] (3) Weigh 365 g of In2O3, 2.5 g of initiator ammonium persulfate, 3.5 g of cross-linking agent N,N-methylenebisacrylamide, 375 g of anhydrous ethanol, 755 g of deionized water, 235 g of chlorogenic acid (CA), and 195 g of glycidyl methacrylate, place them in a reaction vessel, react in a 55°C water bath for 11 h, filter, wash, and dry to obtain a functional filler of the In2O3 / CA / PGMA type, recorded as M4.
[0097] Preparation of thermoplastic resin composites
[0098] (1) 95 parts of PA6, 11 parts of functional filler M4, 0.1 parts of antioxidant Irganox 1010, and 0.2 parts of antioxidant Irganox 1330 were weighed and mixed and stirred to obtain a mixture;
[0099] (2) The mixed material obtained in step (1) is extruded and granulated from a twin-screw extruder to obtain a PA6 composite material, which is denoted as P4.
[0100] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 210°C, the temperature of the second temperature zone is 260°C, the temperature of the third temperature zone is 260°C, the temperature of the fourth temperature zone is 260°C, the temperature of the fifth temperature zone is 260°C, the temperature of the sixth temperature zone is 260°C, the head temperature of the twin-screw extruder is 260°C, and the screw speed is 320r / min.
[0101] Comparative Example 4
[0102] Compared with Example 4, this comparative example only has a different functional filler, and the filler in this comparative example is In2O3 calcined in Example 4. The specific steps for preparing the thermoplastic resin composite material in this comparative example are as follows:
[0103] (1) According to the weight ratio, 95 parts of PA6, 11 parts of In2O3 calcined in Example 4, 0.1 parts of antioxidant Irganox1010, and 0.2 parts of antioxidant Irganox1330 were weighed, mixed and stirred to obtain a mixture;
[0104] (2) The mixed material obtained in step (1) is extruded and granulated from a twin-screw extruder to obtain a PA6 composite material, which is recorded as D4.
[0105] The twin-screw extruder includes six temperature zones arranged in sequence. The temperature of the first temperature zone is 210°C, the temperature of the second temperature zone is 260°C, the temperature of the third temperature zone is 260°C, the temperature of the fourth temperature zone is 260°C, the temperature of the fifth temperature zone is 260°C, and the temperature of the sixth temperature zone is 260°C. The head temperature of the twin-screw extruder is 260°C and the screw speed is 320r / min.
[0106] The PA6 composite materials prepared in Example 4 and Comparative Example 4 were made into specimens using an injection molding machine for testing. The test results are shown in Table 4.
[0107] Table 4 Test results of relevant properties of PA6 composite materials prepared in Example 4 and Comparative Example 4
[0108]
[0109] It can be seen from the test results in Table 4 that the mechanical properties and antibacterial properties of the PA6 composite material prepared in Example 4 are better than those of Comparative Example 4.
[0110] Example 5
[0111] Preparation of functional fillers
[0112] (1) Weigh 385 g of indium nitrate, 295 g of ammonia water, and 735 g of deionized water, place them in a reaction vessel, and stir and react at 58° C. for 7 h to prepare solution A;
[0113] (2) Filter, wash, and dry solution A, and calcine in a muffle furnace at 715° C. for 15 h to obtain In2O3;
[0114] (3) Weigh 335 g of In2O3, 1 g of initiator ammonium persulfate, 4 g of cross-linking agent N,N-methylenebisacrylamide, 385 g of anhydrous ethanol, 755 g of deionized water, 235 g of chlorogenic acid (CA), and 195 g of glycidyl methacrylate, place them in a reaction vessel, react in a 55°C water bath for 11 h, filter, wash, and dry to obtain a functional filler of the In2O3 / CA / PGMA type, recorded as M5.
[0115] Preparation of thermoplastic resin composites
[0116] (1) Weigh 105 parts of PS, 9 parts of functional filler M5, 0.1 parts of antioxidant Irganox 1010, and 0.1 parts of antioxidant Irganox 168 according to weight, mix and stir evenly to obtain a mixture;
[0117] (2) The mixed material obtained in step (1) is extruded and granulated from a twin-screw extruder to obtain a PS composite material, which is denoted as P5.
[0118] The twin-screw extruder includes six temperature zones arranged in sequence, wherein the twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 180°C, the temperature of the second temperature zone is 220°C, the temperature of the third temperature zone is 220°C, the temperature of the fourth temperature zone is 220°C, the temperature of the fifth temperature zone is 220°C, the temperature of the sixth temperature zone is 220°C, the head temperature of the twin-screw extruder is 220°C, and the screw speed is 280r / min.
[0119] Comparative Example 5
[0120] Compared with Example 5, this comparative example only has a different functional filler, and the filler in this comparative example is In2O3 calcined in Example 5. The specific steps for preparing the thermoplastic resin composite material in this comparative example are as follows:
[0121] (1) 105 parts of PS, 9 parts of In2O3 calcined in Example 5, 0.1 parts of antioxidant Irganox1010, and 0.1 parts of antioxidant Irganox168 were weighed and mixed and stirred to obtain a mixture;
[0122] (2) The mixed material obtained in step (1) is extruded and granulated from a twin-screw extruder to obtain a PS composite material, which is recorded as D5.
[0123] The twin-screw extruder includes six temperature zones arranged in sequence, wherein the twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 180°C, the temperature of the second temperature zone is 220°C, the temperature of the third temperature zone is 220°C, the temperature of the fourth temperature zone is 220°C, the temperature of the fifth temperature zone is 220°C, the temperature of the sixth temperature zone is 220°C, the head temperature of the twin-screw extruder is 220°C, and the screw speed is 280r / min.
[0124] Comparative Example 6
[0125] Preparation of thermoplastic resin composites
[0126] (1) 105 parts of PS, 9 parts of In2O3 calcined in Example 5, 6 parts of chlorogenic acid (CA), 0.1 parts of antioxidant Irganox1010, and 0.1 parts of antioxidant Irganox168 were weighed and mixed and stirred to obtain a mixture;
[0127] (2) The mixed material obtained in step (1) is extruded and granulated from a twin-screw extruder to obtain a PS composite material, which is denoted as D6.
[0128] The twin-screw extruder includes six temperature zones arranged in sequence, wherein the twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 180°C, the temperature of the second temperature zone is 220°C, the temperature of the third temperature zone is 220°C, the temperature of the fourth temperature zone is 220°C, the temperature of the fifth temperature zone is 220°C, the temperature of the sixth temperature zone is 220°C, the head temperature of the twin-screw extruder is 220°C, and the screw speed is 280r / min.
[0129] The PS composite materials prepared in Example 5 and Comparative Examples 5-6 were made into specimens using an injection molding machine for testing. The test results are shown in Table 5.
[0130] Table 5 Test results of relevant properties of PS composite materials prepared in Example 5 and Comparative Examples 5-6
[0131]
[0132] It can be seen from the test results in Table 5 that, in general, the mechanical properties and antibacterial properties of the PS composite material prepared in Example 5 are better than those of Comparative Examples 5-6.
[0133] The comparison between the above embodiments and comparative examples shows that the thermoplastic resin composite material prepared by the method provided in the present invention has excellent mechanical properties and antibacterial properties, which expands the application field of the thermoplastic resin composite material.
[0134] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0135] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A method for preparing a functional filler, characterized in that: The following steps are involved: Get In2O3; In2O3, an initiator, a cross-linking agent, anhydrous ethanol, deionized water, chlorogenic acid, and glycidyl methacrylate were reacted in a water bath at 40-60°C for 8-12 hours to obtain a functional filler having a composition of In2O3 / CA / PGMA.
2. The method for preparing the functional filler according to claim 1, characterized in that: The preparation of In2O3 comprises the following steps: Take indium nitrate, ammonia water and deionized water, stir and react at 40-60°C for 6-8h to prepare solution A; The solution A is filtered, washed, dried, and then calcined at 680-720° C. for 8-16 hours to obtain In 2 O 3 .
3. The method for preparing the functional filler according to claim 2, characterized in that: In the step of preparing solution A, the mass ratio of indium nitrate, ammonia water and deionized water is (30-40): (28-32): (60-80).
4. The method for preparing the functional filler according to claim 1, characterized in that: The mass ratio of In2O3, initiator, cross-linking agent, anhydrous ethanol, deionized water, chlorogenic acid and glycidyl methacrylate is (30-40): (0.1-0.3): (0.2-0.4): (30-40): (60-80): (18-24): (16-20).
5. The method for preparing the functional filler according to claim 1, characterized in that: The initiator is ammonium persulfate; the cross-linking agent is N,N-methylenebisacrylamide.
6. Use of a functional filler prepared by the method for preparing a functional filler according to any one of claims 1 to 5 in preparing a thermoplastic resin composite material.
7. A thermoplastic resin composite material, characterized in that: The invention is prepared from 80-120 parts of thermoplastic resin, 8-12 parts of functional filler and 0.1-0.5 parts of antioxidant according to weight parts; Wherein, the functional filler is prepared by the preparation method according to any one of claims 1 to 5.
8. The thermoplastic resin composite material according to claim 7, characterized in that The thermoplastic resin is selected from one of polyethylene (PE), polypropylene (PP), polystyrene (PS), polybutylene terephthalate (PBT), and polyamide 6 (PA6).
9. The thermoplastic resin composite material according to claim 7, characterized in that: The antioxidant is selected from one of antioxidant 168, antioxidant 1010, and antioxidant 1330, or a mixture of two or more thereof.
10. A method for preparing a thermoplastic resin composite material according to any one of claims 7 to 9, characterized in that: The following steps are involved: The thermoplastic resin, the functional filler and the antioxidant are uniformly mixed according to a ratio to obtain a mixture; The mixed material is extruded and granulated through a twin-screw extruder to obtain a thermoplastic resin composite material.
Citation Information
Patent Citations
Antibacterial agent as well as preparation method and application thereof
CN115088736A
Heat-conducting antibacterial thermoplastic resin composite material and preparation method thereof
CN116285112A